Contributions to the thermophilous fringe communities (Trifolio-Geranietea sanguinei) in Belarus - Iakushenko, Dmytro (Biodiversity: Research and Conservation, 2017)
The paper presents the results of phytosociological studies on thermophilous forb fringes conducted in August, 2012, in Belarus. A dataset of 31 relevés is analyzed, 3 associations and 1 community of 3 alliances and 3 orders of the class Trifolio-Geranietea sanguinei T. Müller 1962 are distinguished. For the first time for this area, the association Galio borealis- Geranietum sanguinei Tüxen 1967 is reported and characterized. The results of syntaxonomical interpretation are discussed based on chorological data.